PEMBAHARUAN SISTEM PENDIDIKAN PESANTREN DALAM MENGAHADAPI TANTANGAN ERA GLOBALISASI - Miftahul Huda; Andewi Suhartini; Nurwadjah Ahmad Eq (IAIN Pontianak, 2022)
One of the characteristics of the community is that there is continuous change, always experiencing dynamics and developments due to the demands of the times. This includes Islamic boarding schools. This study discusses the renewal of the pesantren education system in the face of the era of globalization. So the purpose of this research is to formulate the strategies needed to deal with it. The approach used in this research is a qualitative approach which is library research. The results of this study show that the key to the survival of pesantren to continue to exist in facing the challenges of globalization is renewal in: 1) aspects of goals, 2) aspects of organization, 3) aspects of curriculum, 4) aspects of learning methods, 5) aspects of educators, and 6) aspects of students.Keywords: Renewal, Pesantren Education, Strategy, Globalization.